CT SCAN OF INTRACRANIAL AIR EMBOLISM: POST CARDIOPULMONARY RESUSCITATION - VISUDTIBHAN, Anannit; PEKANAN, Patchrin; PONGPECH, Sirintara; JAOVISIDTH, Suphaneewan; W PREIDLER, Klaus (The ASEAN Journal of Radiology, 2023)
A case report of intracranial intravascular air detected by CT scan was per- formed. The images obtained immediately after the patient expired post failed cardio- pulmonary resuscitation in an 11-year-old child who had unknown cause of hepatitis.